49 Years Emerging of Environmental Performance: A Systematic Literature Review - Vitriyan Espa; Soeprajitno, Raden Roro Widya Ningtyas; Marsela Diaz (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
This study aims to analyze trends, progress, and opportunities for future research. This study reviews 49 years of emergence of environmental performance through systematic literature and conducts content analysis. The data for this study were obtained from 244 sample articles from the period 1972 to November 2021 based on the SCOPUS database. The findings we obtained show trends in topic classification, research settings, theories, methods and analysis techniques as well as suggestions for further research. We classified 10 themes of research topics; Management Strategy; Financial and Corporate Performance; Management information System; Characteristics of Corporate Governance; Green Supply Chain Management; Requests for Environmental Performance Information Exist; Green Human Resource Management; Organizational Behavior; Environmental Regulations; Security Market Returns.